Tracking the educationalization of the world: Prospects for an emancipated history of education - Tröhler, Daniel (Education Policy Analysis Archives, 2018)
This article reconstructs the rise, the national differentiations and the decline of the genre history of education and outlines subsequently what the history of education could mean if it emancipated itself from the conditions that led to its emergence, religion and nationalism – conditions, that, nota bene, are by no means as dominant as they once were.